The Role of Teachers in Getting Used to Singing National Ants as an Effort to Form Students’ Nationalism - Imam Siddiq (International Journal of Students Education, 2024)
This research aims to find out the extent of the role of teachers in getting used to singing national songs as an effort to form students’ nationalism, secondly the role of national songs in forming students’ spirit of nationalism, then thirdly the obstacles to teachers getting used to singing national songs in forming students’ love of their homeland. The research method used in this article is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practitioners. The research results show that the teacher’s job is to set an example, create a conducive educational environment, guide teaching and training of students and foster a spirit of nationalism. The aim is, in order to foster a spirit of nationalism, teachers must have a high spirit of nationalism and patriotism, have a national perspective and recognize symbols. state symbol. When the researcher made observations, the teacher’s task in cultivating the spirit of nationalism was conveyed well as seen from the teacher always linking PPKn material with the spirit of nationalism, but there were still many students who did not memorize the national song, making teachers have to be more creative in getting used to singing the national song so that there were no Moreover, students do not know the national song by heart, so students have an interest in the national song.